The Effect of Waiting Time for Doctor's Services on Patient Satisfaction in the Outpatient Department of RSUD Toto Kabila - Fuji Fauzia H. Yakop; Titin Dunggio; Serly Daud (Journal of Health, Technology and Science (JHTS), 2021)
This study aims to determine the effect of waiting time for doctor's services on patient satisfaction in the Outpatient Department of RSUD Toto Kabila. This study aims to determine whether there is an effect of waiting time for doctor's services on patient satisfaction in the outpatient department of RSUD Toto Kabila which is seen from the waiting time and the five "RATER" dimensions of reliability, assurance, tangibles, empathy and responsiveness. This type of research uses a quantitative approach. The type of data used is cross-sectional which aims to analyze the relationship between the independent variable (Waiting Time) and the dependent variable consisting of (Reliability, Assurance, Tangible, Empathy, Responsiveness) IN Outpatient Hospital Tototo Kabila. The sample of this study amounted to 52 people consisting of surgical polyclinic patients in the outpatient installation of RSUD Toto Kabila. Collecting data using a questionnaire (questionnaire) which is then analyzed using the chi-square test. The results showed that the effect of waiting time for doctor's services on patient satisfaction at Toto Kabila Hospital, the results of the Hypothesis Test that had been carried out showed that there was an effect of waiting time for doctor's services on patient satisfaction with the sign value. 0.00 < 0.05, then H0 is rejected and H1 is accepted. So the researchers concluded that there was an effect of waiting time on patient satisfaction in the outpatient installation of RSUD Toto Kabila.